2013
DOI: 10.1099/jmm.0.058636-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of 16S RNA nucleotide sequences of Anaplasma phagocytophilum detected in the blood of horses from various parts of Europe

Abstract: The aim of this study was to conduct a comparative analysis of the 16S rRNA gene fragment nucleotide sequences for Anaplasma phagocytophilum strains detected in the blood of horses from various parts of Europe. The study comprised 234 horses that had had contact with ticks. Using PCR, the genetic material of A. phagocytophilum was identified in the blood of 42 animals. The sequences of the 16S RNA gene amplicons that were obtained from our A. phagocytophilum isolates had 100 % similarity with each other and 96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Infections with A. phagocytophilum , the causative agent of human granulocytic anaplasmosis, have been increasingly diagnosed in both companion and farm animals in Poland (Adaszek et al 2009 ; Zygner et al 2009 ; Dzięgiel et al 2013 ). This pathogen has also been found in the blood of game animals (Adaszek et al 2012 ; Dzięgiel et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Infections with A. phagocytophilum , the causative agent of human granulocytic anaplasmosis, have been increasingly diagnosed in both companion and farm animals in Poland (Adaszek et al 2009 ; Zygner et al 2009 ; Dzięgiel et al 2013 ). This pathogen has also been found in the blood of game animals (Adaszek et al 2012 ; Dzięgiel et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we cannot exclude that horses in this study had previously been in contact with this pathogen. It is discussed that climate change might increase the threat of disease in European horse populations (41).…”
Section: Discussionmentioning
confidence: 99%
“…10 Recently, a 16S rRNA nucleotide sequences investigation reported a new rickettsial genotype in horses in southern and eastern Europe. 11 Moreover, this gene (EC9/EC12a and SSAP2f/SSAP2r primer set) is quite accurate for the diagnosis of A. phagocytophilum DNA in ruminants and ticks. 12 Some studies conducted in Turkey have been reported DNA positivity for A. phagocytophilum in dogs, cattle, sheep and tick.…”
Section: Introductionmentioning
confidence: 98%